1995
DOI: 10.1038/nm0695-578
|View full text |Cite
|
Sign up to set email alerts
|

The drug resistance-related protein LRP is the human major vault protein

Abstract: Multidrug-resistant cancer cells frequently overexpress the 110-kD LRP protein (originally named Lung Resistance-related Protein). LRP overexpression has been found to predict a poor response to chemotherapy in acute myeloid leukaemia and ovarian carcinoma. We describe the cloning and chromosome localization of the gene coding for this novel protein. The deduced LRP amino acid sequence shows 87.7% identity with the 104-kD rat major vault protein. Vaults are multi-subunit structures that may be involved in nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
368
0
9

Year Published

1996
1996
2002
2002

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 556 publications
(380 citation statements)
references
References 22 publications
3
368
0
9
Order By: Relevance
“…Also, no detectable levels of P-glycoprotein were observed in any of the ovarian cell lines and in the SKOV3-puro and SKOV3-S2 lines (data not shown). The role of another newly described protein associated with multidrug resistance, termed the lung resistance protein (LRP or 1 10-kDa human vault protein) (Scheffer et al, 1995). was investigated in our panel of cisplatinsensitive and -resistant cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Also, no detectable levels of P-glycoprotein were observed in any of the ovarian cell lines and in the SKOV3-puro and SKOV3-S2 lines (data not shown). The role of another newly described protein associated with multidrug resistance, termed the lung resistance protein (LRP or 1 10-kDa human vault protein) (Scheffer et al, 1995). was investigated in our panel of cisplatinsensitive and -resistant cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…cDNA library and isolation of the LMR-12 cDNA clone Previously, a cDNA-library was derived from mRNA isolated from the human MDR fibrosarcoma cell line HT1080/DR4 (Scheffer et al, 1995). Briefly, a size-fractionated (42 kbp) oligo d(T) primed cDNA-library was constructed in the shuttle vector pCDM8 using non-self complementary BstXI adaptors (Invitrogen, Leek, The Netherlands).…”
Section: Facs Analysismentioning
confidence: 99%
“…Also, immunoprecipitation experiments did not reveal the antigen. Therefore, the expression cloning system that had succesfully been used to identify the nature of the LRP-56 Mab (Scheffer et al, 1995) was also used here. MOP8 cells were transiently transfected with pCDM8 vector, containing cDNA inserts of the MDR fibrosarcoma cell line HT1080/DR4 and screened for LMR-12 immunoreactivity.…”
Section: Frequent Lmr-12 Staining In Tumour Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have identified Human lymphocytes from the venous blood of a donor were MRP and LRP as two other drug resistance related proteins retrieved by separation on a Ficoll-Hypaque gradient involved in cellular drug transport, subcellular distribution (Histopaque 1077; Sigma Chemical, St Louis, MO, USA) The and resistance. 3,4 mononuclear cells were washed and resuspended in miniBesides immunocytochemistry which depends on the use of mum essential medium and 4% heat inactivated fetal bovine monoclonal antibodies for identification of cellular resistance serum. The lymphocytes, at a starting concentration of markers, fluorescent microscopy and confocal microscopy 1 × 10 6 /ml, were cultured in flasks containing 18 ml of cell and laser flow cytometry have been used to study transport suspension and 2 ml of 200 g/ml phytohemagglutinin-P and subcellular distribution of fluorescent drugs.…”
mentioning
confidence: 99%